Characterization of a metalloprotease inhibitor protein (SmaPI) of Serratia marcescens. - Kim, K S (1995)
As suggested by Y. Suh and M.J. Benedik (J. Bacteriol. 174: 2361-2366, 1992), Serratia marcescens ATCC 27117 produced very small amounts (0.8 U ml-1) of an inhibitor protein (SmaPI) that shows an inhibitory activity against extracellular 50-kDa metalloprotease (SMP) of S. marcescens and that is localized in the periplasm of cells at the optimal growth temperature of 25 degrees C. A recombinant S. marcescens harboring plasmid pSP2 encoding SMP and SmaPI genes produced 20 U of SmaPI ml-1 that is also localized in the periplasm of cells at 25 degrees C. However, a large amount of SmaPI (86 Uml-1) was extracellularly produced at the supraoptimal growth temperature 37 degrees C from the recombinant S. marcescens (pSP2). We purified SmaPI from the culture supernatant of S. marcescens (pSP2) grown at 37 degrees C, and some biochemical properties were characterized. SmaPI had a pI value of about 10.0 and was a monomeric protein with a molecular mass of 10,000. SmaPI was produced from a precursor SmaPI by cleavage of a signal peptide (26 amino acid residues). The inhibitor was stable in boiling water for up to 30 min. The thermostability of SmaPI can be attributed to its reversible denaturation. SmaPI inhibited SMP by formation of a noncovalent complex with a molar ratio of 1:1 and showed a high protease specificity, which inhibited only SMP among the various proteases we examined.